Dosing physical loads in the health improving physical training for the persons with the excess mass of body - Bochkova N.L (Kharkov National Pedagogical University, 2010)
The article is devoted to the determination of the parameters of health improving physical training for persons with the excess mass of body. The persons with an excess mass of body of up to 15%, from 15% to 30% and more than 30% were investigated on the antropometric, ergometric, metabolic indices, functional indices of cardiovascular and respiratory systems in the state of relative muscular rest, under the conditions of the standard physical load of 50 W, tolerant and maximum loads. The parameters determination of health improving physical training for the persons with the excess mass of body must be based on the special features of adaptation to the physical loads.